(untitled) (Journal of Environmental Science and Natural Resources, 2015)
Southwestern coastal Bangladesh is characterized by low-lying topography, high productive mangrove ecosystem and unique biodiversity. At the same time, the region is highly prone to cyclones, coasting flooding, and salinity, which causes huge losses to agriculture production and rural livelihoods. Marginal and small farmers are affected more. The objective of this paper is to examine the extent of climatic variations and to analyze farming communities vulnerabilities and adaptations to climate change in the saline prone southwestern coastal Bangladesh. We used both primary and secondary data for this study. We collected primary data from Atulia and Padmapukur unions of Shyamnagar upazila under Satkhira district of Bangladesh in April 2013. We collected secondary data from published statistics. We did not find significant changes in temperature and rainfall over time but salinity level has increased over time. Major vulnerability faced by farming communities due to climate change were saline water intrusion, scarcity of safe drinking and irrigation water, and problems on crop production, livestock rearing, fresh water fish culture, and sanitary latrines. Major adaptations practiced by farmers were culturing saline water shrimp in farms, harvesting rain water, drinking ponds water, catching fish from the sea and river, and desalinization of river water by constructing embankments. Agricultural adaptation practices such as saline tolerant rice varieties cultivation, crabs fattening, sowing and planting date shifting, mulching, soil flashing, fertilizers management, seeds sowing using dibbling method, raise or slopping bed method crop cultivation in embankments, pit method crop cultivation, changing cropping patterns, zero tillage, and sorjan method crop cultivation can helps minimize the impacts of climate change, particularly to vulnerable smallholder farmers. Policies and programs are needed to develop and disseminate these adaptation practices complemented by farmers training on these practices. DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22200 J. Environ. Sci. & Natural Resources, 7(2): 31-35 2014